ADCY5-related dyskinesia: Broader spectrum and genotype–phenotype correlations. (8th December 2015) - Chen, Dong-Hui; Méneret, Aurélie; Friedman, Jennifer R.; Korvatska, Olena; Gad, Alona; Bonkowski, Emily S.; Stessman, Holly A.; Doummar, Diane; Mignot, Cyril; Anheim, Mathieu; Bernes, Saunder; Davis, Marie Y.; et al.
Abstract : Objective: To investigate the clinical spectrum and distinguishing features of adenylate cyclase 5 ( ADCY5 )–related dyskinesia and genotype–phenotype relationship. Methods: We analyzed ADCY5 in patients with choreiform or dystonic movements by exome or targeted sequencing. Suspected mosaicism was confirmed by allele-specific amplification. We evaluated clinical features in our 50 new and previously reported cases. Results: We identified 3 new families and 12 new sporadic cases with ADCY5 mutations. These mutations cause a mixed hyperkinetic disorder that includes dystonia, chorea, and myoclonus, often with facial involvement. The movements are sometimes painful and show episodic worsening on a fluctuating background. Many patients have axial hypotonia. In 2 unrelated families, a p.A726T mutation in the first cytoplasmic domain (C1) causes a relatively mild disorder of prominent facial and hand dystonia and chorea. Mutations p.R418W or p.R418Q in C1, de novo in 13 individuals and inherited in 1, produce a moderate to severe disorder with axial hypotonia, limb hypertonia, paroxysmal nocturnal or diurnal dyskinesia, chorea, myoclonus, and intermittent facial dyskinesia. Somatic mosaicism is usually associated with a less severe phenotype. In one family, a p.M1029K mutation in the C2 domain causes severe dystonia, hypotonia, and chorea. The progenitor, whose childhood-onset episodic movement disorder almost disappeared in adulthood, was mosaic for the mutation. Conclusions: ADCY5 -related dyskinesia is a childhood-onset disorder with a wide range of hyperkinetic abnormal movements. Genotype-specific correlations and mosaicism play important roles in the phenotypic variability. Recurrent mutations suggest particular functional importance of residues 418 and 726 in disease pathogenesis.